Integrasi Pendidikan Multikultural dalam Pembelajaran Sejarah di Madrasah Aliyah Tahfizhil Qur’an - Rukun Sembiring; Dicki Pratama; Shamry Bermansah Silalahi; Rikardo Rajagukguk; Hafnita Sari Dewi Lubis (Program Studi Pendidikan Biologi, 2022)
Multicultural education is important in school life. The problem of this research is how the integration of multicultural education in history learning. The purpose of this study is to determine the integration of multicultural education in the material of history learning material in ma Tahfizhil Qur'an. The results showed that teachers of History subjects integrated multicultural education in history learning at MA Tahfizhil Qur'an. The learning method uses a varied lecture method by providing equal opportunities and rights to students, as well as relating historical relics in the form of local sites in North Sumatra Province such as the Chinese City Site with the aim of respecting sites from other religions, from other groups, as well as from people in other regions by tolerating religion, race, nation to other tribes Multicultural education in the learning carried out can form a good relationship of tolerance between learners.